Comparing the nature of the workplace bullying in two european countries: Portugal and UK - Jennifer, Dawn (2000)
Adult bullying in the workplace has been the focus of systematic international study for the last five years but there are a few cross-cultural comparisons of the phenomenon. In this paper, we report the findings from a cross-cultural investigation into employees perception of socil and organizational work conditions and experiences of bullying and social exclusion at work. Employees from companies im Portugal and the UK completed the Workplace Relationships Questionnaire (WRQ). We present the results of the analysis of the link between: a)who is bullied and who bullies; b) the extent to which bullying affects victims and non.bullied colleagues. We discuss the diferences and similarities between the two countries and some of the benefits that arise from doeng cross-cultural research.